Anomalous transport and diffusion in percolation systems - Bunde, Armin; Heitjans, Paul; Indris, Sylvio; Kantelhardt, Jan W.; Ulrich, Markus (Diffusion Fundamentals, 2007)
Many disordered systems can be modelled by percolation. Applications of this standard model range from amorphous and porous media to composites, branched polymers, gels and complex ionic conductors. In this brief review we give a short introduction to percolation theory and describe applications in materials science. We start with the structural properties of percolation clusters and their substructures. Then we turn to their dynamical properties and discuss the way the laws of diffusion and conduction are modified on these structures. Finally, we review applications of the percolation concept for transport in various kinds of heterogeneous ionic conductors.